2020
DOI: 10.1186/s12883-020-01848-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with insufficient response to acute treatment of migraine in Japan: analysis of real-world data from the Adelphi Migraine Disease Specific Programme

Abstract: Background: Real-world data on sufficient/insufficient response, and predictors of insufficient response, to acute treatments for migraine are limited in Japan. This study aimed to identify factors associated with insufficient response to acute treatment of migraine by exploring significant differences between people with migraine who sufficiently/insufficiently respond to prescribed acute treatment in Japan. Methods: This was a retrospective analysis of 2014 Adelphi Migraine Disease Specific Programme cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 34 publications
(57 reference statements)
4
16
1
Order By: Relevance
“…In contrast, this analysis of the 2017 Japan Adelphi Migraine DSP identified no significant differences in any concomitant comorbidities between TIRs and TSRs. A similar finding was reported in the 2014 Japan Adelphi Migraine DSP analysis, which aimed to identify factors associated with an insufficient response to acute medication (including but not limited to triptans) in people with migraine [8]. These differences between analyses of global and Japan Adelphi Migraine DSP data may reflect differences in the health care systems of Japan and the countries included in the global analysis.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In contrast, this analysis of the 2017 Japan Adelphi Migraine DSP identified no significant differences in any concomitant comorbidities between TIRs and TSRs. A similar finding was reported in the 2014 Japan Adelphi Migraine DSP analysis, which aimed to identify factors associated with an insufficient response to acute medication (including but not limited to triptans) in people with migraine [8]. These differences between analyses of global and Japan Adelphi Migraine DSP data may reflect differences in the health care systems of Japan and the countries included in the global analysis.…”
Section: Discussionsupporting
confidence: 62%
“…triptans for the treatment of migraine [43] and of patients' willingness to continue with their current prescribed acute therapy for migraine [8]. In the current analysis, although a high proportion of patients reported that they were satisfied with their prescribed triptan acute medication, TIRs were more likely than TSRs to express lower levels of satisfaction, or even dissatisfaction, a finding also reported in the global analysis of 2017 Adelphi Migraine DSP data [28].…”
Section: 0425supporting
confidence: 61%
See 3 more Smart Citations